Scale-Up Marketing and Export of MSME Products Based on Digital Business at MEK-PDM Gresik - Efta Dhartikasari Priyana; Abdurrahman Faris Indriya Himawan (Kontribusia : Research Dissemination for Community Development, 2022)
The low quality of Human Resources which ultimately leads to the ineffectiveness of management, organization and technology has made the development of MSMEs in Indonesia unable to touch rapidly. Plus the large transaction costs from the impact of an unfavorable business climate are also a problem for the case of MSMEs fostered by MEK-PDM Gresik, making it difficult to compete in the international market. In fact, the products produced by MSMEs are no less competitive with those produced by foreign products. In fact, to be able to penetrate the global market, MSMEs must at least be able to adapt to the concept of global marketing which is not yet owned by MSME stakeholders. Therefore, in this service, MSME actors will be taught how to market their products globally. Fronted by Dr. Indro Kirono as a performer who previously had a long history in the export world, the service event went more than imagined. Many MSME products were independently assisted by the presenters to be introduced a little in the global market. Gresik UMKM products will also be assisted by the introduction of Gresik Muhammadiyah University. So that Muhammadiyah University of Gresik can become a place for Gresik SMEs to be fostered.